Keris Dhapur Inu: Inovasi Dhapur Klasik Berbahan Mangalloy Sebagai Penghasil Pamor - Bening Tri Suwasono; Muh. Arif Jati Purnomo (UNIVERSITAS INDO GLOBAL MANDIRI, 2025)
This research represents an effort to develop form and material in the art of tosan aji (sacred metalwork) through the creation of the Keris Dhapur Inu. The formal inspiration is drawn from the character Panji Inu Kertapati, who embodies the refined and wise qualities of a noble Javanese knight. The urgency of this study lies in the limited exploration of alternative materials capable of producing pamor (surface patterns on keris blades) and the scarcity of new dhapur innovations grounded in the cultural symbolism of the Panji tradition. The research problem is addressed through an art-based applied research approach focusing on material experimentation and innovation in dhapur design. This study aims to identify the characteristics of Mangalloy as an alternative pamor-producing material, develop a new dhapur form rooted in Panji symbolism, and realize a keris artwork that synthesizes modern metallurgical knowledge with the traditional values of tosan aji. The primary material used is manganese alloy steel (Mangalloy), which was initially misidentified as ataxite meteoritic iron. X-ray Fluorescence Spectrometer analysis—employed for non-destructive chemical composition identification—shows that the material contains high Fe–Mn and low nickel content, classifying it as manganese steel. Through processes of fold-forging, shaping, tinatah carving of Panji mask motifs on the gandhik (facial section of the blade), and pewarangan (blade finishing), the research produces a keris with strong contrast pamor and dense metal structure. Dhapur Inu emerges as a synthesis of modern metallurgy and tosan aji traditions, demonstrating the potential of Mangalloy as an alternative metal for generating pamor.